Secreted Cyclic Di-GMP Induces Stalk Cell Differentiation in the Eukaryote Dictyostelium discoideum - Chen, Zhi-hui; Schaap, Pauline (Journal of bacteriology, 2016)
Cyclic di-GMP (c-di-GMP) is currently recognized as the most widely used intracellular signal molecule in prokaryotes, but roles in eukaryotes were only recently discovered. In the social amoeba Dictyostelium discoideum , c-di-GMP, produced by a prokaryote-type diguanylate cyclase, induces the differentiation of stalk cells, thereby enabling the formation of spore-bearing fruiting bodies. In this review, we summarize the currently known mechanisms that control the major life cycle transitions of Dictyostelium and focus particularly on the role of c-di-GMP in stalk formation. Stalk cell differentiation has characteristics of autophagic cell death, a process that also occurs in higher eukaryotes. We discuss the respective roles of c-di-GMP and of another signal molecule, differentiation-inducing factor 1, in autophagic cell death in vitro and in stalk formation in vivo .